Did the romans introduce the Egyptian mongoose (Herpestes ichneumon) into the Iberian Peninsula? - Detry, Cleia (2018)
New finds of bones of the Egyptian Mongoose (Herpestes ichneumon), one from Portugal and one from Spain, were directly ¹⁴C dated to the first century AD. While the Portuguese specimen was found without connection to the Chalcolithic occupation of the Pedra Furada cave where it was recovered, the Spanish find, collected in the city of Mérida, comes from a ritual pit that also contained three human and 40 dog burials. The finds reported here show that the Egyptian mongoose, contrary to the traditional and predominant view, did not first arrive in the Iberian Peninsula during the Muslim occupation of Iberia. Instead, our findings are consistent with the hypothesis that the species was first introduced by the Romans, or at least sometime during the Roman occupation of Hispania. Therefore, radiocarbon dating of new archaeological finds of bones of the Egyptian Mongoose (Herpestes ichneumon) in the Iberian Peninsula push back the confirmed presence of the species in the region by approximately eight centuries, as the previously oldest dated record is from the ninth century. With these new dates, there are now a total of four ¹⁴C dated specimens of Egyptian mongooses from the Iberian Peninsula, and all of these dates fall within the last 2000 years. This offers support for the hypothesis that the presence of the species in Iberia is due to historical introductions and is at odds with a scenario of natural sweepstake dispersal across the Straits of Gibraltar in the Late Pleistocene (126,000–11,700 years ago), recently proposed based on genetic data.